Knowledge and attitude toward elderly among registered nurses in Hospital Universiti Sains Malaysia (Hospital USM) - Jamaludin, Nurul Hazreena (2020)
The elderly defined as those aged 60 or above that equivalent to retirement ages (World Health Organization, 2016). As the increasing of the elderly population, the need of registered nurses with the right attitude, adequate knowledge and skill also must be on the increase. A cross-sectional study was carried out to study the knowledge and attitude toward the elderly among registered nurses in Hospital USM. The questionnaire used in this study was a self-administered questionnaire and for knowledge and attitude, the questionnaires was adapted from Palmore (1988) and Hilt & Lipschultz (1997). A total of 75 registered nurses in Hospital USM who fulfilled the inclusion and exclusion criteria were selected randomly. Data collected were statistically analyzed using the SPSS software version 24.0. Fisher’s exact test was used for data analysis. As for the level of knowledge and attitude, the results show 49 (65.3%) for high knowledge and 65 (86.7%) for positive attitude respectively. Next is there is no association between course education and working experience with the level of attitude toward the elderly (p = 1.000) and (p = 0.484) respectively. Lastly, there was no association between level of knowledge and attitude (p = 0.731), the results show only 43 (87.8%) for respondents who have high knowledge and positive attitude. In conclusion, the level of the knowledge and attitude need to be increased and improved among registered nurses as they will be more knowledgeable and skilful in delivering care toward the elderly.